COMPETENCE APPROACH TO MANAGING STUDENTS’ TRAINING FOR SUCCESSFUL CAREER - Kondrashov, Nykolay Nykolayevych (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2018)
Introduction The article describes the training of management capabilities of students for a successful career built on the basis of competence-based approach; Specify the goal, objectives, a set of skills and competencies to ensure the success of a professional identity, strategic directions for its implementation in the educational process; identifies conditions that ensure the effectiveness of training students for professional management activities. The purpose of this article is to identify and theoretical justification success training strategy, the formation of the professional image of a successful business man and professional success can not be achieved only by means of knowledge and professional skills. Nowadays, the role of the personal potential of the teacher, his/her readiness to successful learning of students, which resulted in a successful person. Results. Substantiates conditionality focus management actions for the implementation of the competency approach to the preparation of students in the system of university education such dominant: personal-professional orientation of the educational process; reorientation of the position of each student to self-actualization and self-empowerment efforts in training activities; activity character education – convert learned knowledge in practical action tool, a tool for solving professional problems; self-realization, self-development, self-assertion in the educational activity, the development of the ability to act independently, make decisions, be responsible for their consequences; didactic interaction, collaboration and co-creation in «teacher – student» system in order to successfully achieve the planned results in the training activities and the implementation of individual strategies for the development of their professional image; variability in achieving the projected goals; focus on the individuality of the person, the development of individual style of activity and an active position; the implementation of individual programs of self-development. The article reveals the strategy of educational activity as the main directions of optimization of preparation of students for successful professional activity: the mastery of modeling techniques of different activities to achieve success in learning situations professional orientation; humanization of relations «teacher – student» system; activation of cognitive position of students in the learning process; transformation of knowledge learned in the professional values and personal meanings; Purposeful work on the development of the creative potential of the person of students; creation of a system of timely psychological support and educational assistance to each student in a university education. Strategic directions of influence and the nature of the educational process are represented. Conclusion. The effectiveness of the control preparation of students for successful professional activity of his organization determined on the basis of competence approach. The main conditions for the successful achievement of professional competence of students as a pledge of their success in professional activity are: increasing the efficiency of each class as a dialogue of the teacher and students; use a variety of technologies that ensure the success of the students acquire experience and develop professional competencies; create a situation of success in educational process; teacher-orientation on the personal achievements of students; providing each student the freedom to choose, feedback and comfort in the learning process; psychological and pedagogical support activities of students in the learning process.